Estimation of the prevalence and determination of risk factors associated with demodicosis in dogs - Rahman, Mizanur; Bostami, Mohammad Bayazid; Datta, Aparna; Sabuj, Abdullah Al Momen; Rana, Eaftekhar Ahmed; Mannan, Abdul; Hossain, Mir Md Afzal; Chowdhury, Mohammed Yousuf Elahi (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: Demodicosis is a vital skin problem in dogs. The present study has determined the prevalence and associated risk factors of demodicosis in dogs and the response to treatment. Materials and Methods: A total of 100 skin scrapings were collected from dogs having dermatological lesions brought to the Teaching and Training Pet Hospital and Research Center of Chattogram Veterinary and Animal Sciences University for treatment purpose. The collected scrapings were dissolved in 10% potassium hydroxide to detect mites through microscopic examination. Various risk factors like breed, age, sex, hair type, health status, and management system (indoor and outdoor) were analyzed using the logistic regression model. Positive cases were treated with oral ivermectin (Scabo®; at 0.6 mg/kg/day) along with amitraz 12.5% (Ridd®) diluted to 0.05% for rubbing on the body after bathing with chlorhexidine shampoo (PetHex®). Clavulanate amoxicillin (Moxaclav®) and omega-3 fatty acids (OMG-3®) were also suggested to prevent secondary bacterial infection and to maintain skin and hair coat integrity. The recovery rate was observed every 2–4 weeks of treatment upto 11–13 weeks. Results: The overall prevalence of demodicosis was recorded as 27%. Hair type, health status, and management system were significantly (p < 0.05) associated with the occurrence of demodicosis in dogs. Following treatment, the first negative skin scraping for mite was noticed at 8–10 weeks of treatment, and in all cases, clinical signs completely disappeared at 80–90 days of treatment. Conclusion: A good percentage of the dogs having dermatological lesions was determined as demodicosis. Long-term oral ivermectin and topical amitraz, an oral antibiotic, and nutritional therapy are effective against canine demodicosis. Keeping long-haired dogs with good body condition and indoor management is highly suggestive of preventing and controlling the disease. J. Adv. Vet. Anim. Res., 8(1): 116-122, Mar 2021 http://doi.org/10.5455/javar.2021.h493